Menggali Potensi Ekonomi Desa Lubuk Sao, Nagari Dalko, Kabupaten Agam : Analisis PESTEL & SWOT untuk Pengembangan Berkelanjutan - Dinda Retno Andjarweni; Rakan Musyafa; Fransiskus Silalahi; Firzha Maharani (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Jorong Lubuk Sao, located in Nagari Dalko, Agam Regency, has great potential in the plantation, fisheries, and agriculture sectors. This study systematically examines the external factors influencing economic development in Jorong Lubuk Sao through an integrated PESTEL-SWOT analytical framework. Qualitative research methods were applied through observation and interviews with local economic actors. The findings reveal that six key external dimensions – political, economic, socio-cultural, technological, ecological, and regulatory aspects – substantially influence the village's economic progression. Furthermore, the SWOT examination pinpoints internal capabilities and limitations, along with external prospects and risks, which collectively shape the community-driven tourism development initiatives. This study recommends the need to enhance community awareness, improve promotion efforts, and secure government support to achieve sustainable economic development.